A Bibliometric Review on Readiness for Change and Organizational Change - Natalia, Vina; Ekowati, Dian (PT Mattawang Mediatama Solution, 2024)
This research aims to determine the development of readiness for change research trends both at the individual and organizational levels published in leading Scopus-based journals. The search process with the categories